Don Presley - SJSU Special Collections & Archives::::::::: (2022)
Don Presley attended San Jose State College from 1937-1940. Presley was active in several sports, including football, heavyweight boxing, and track and field. In 1938, Presley and fellow Black students William Lewis and Lloyd Thomas performed the "Truckin'" dance craze of the time as part of the Spartan Revue. That year he and his dance partner also won "Leading Campus Dancers" at the Press Club contest at the Student Union. In 1939, he lettered in Varsity Football. After graduation, Presley had a short career as a professional heavyweight boxer, from 1940-1941.